Antidepressant use in pregnancy and the risk of neonatal outcomes: a scoping review - Febrianti, Yosi (Universitas Islam Indonesia, 2024)
Background: Depression is a frequently encountered issue during pregnancy and postpartum. Both depression itself and the use of antidepressant medications can have implications for the infant's well-being. Studies have linked maternal depression to adverse outcomes like preterm birth, low birth weight, fetal growth restriction, and potential cognitive and emotional challenges for the child after birth. On the other hand, exposure to antidepressants during pregnancy has been associated with an increased risk of preterm birth, a decrease in birth weight, and congenital malformations. Objectives: In light of these considerations, a scoping review was conducted to examine recent research findings concerning antidepressant use during pregnancy.Methods: This study was a scoping review. Pubmed and Scopus databases were used to search for all relevant studies published from 2019 until 2023. Studies were excluded if they were case reports, narrative reviews, systematic reviews, or meta-analyses. Finally, all eligible articles were assessed for their outcomes. Results: The use of SSRIs and duloxetine antidepressants in perinatal women was linked to preterm birth and smaller gestational sizes compared to controls, according to three cohort studies. Congenital malformation was also associated with duloxetine, mirtazapine, and atomoxetine use during pregnancy (3 cohort studies). Conclusions: Recognizing the potential risks to the infant and the risk of leaving maternal depression untreated is crucial when making the decision to use antidepressants during pregnancy. This underscores the importance of a thoughtful and informed approach to managing depression in pregnant women.Keywords: Antidepressant, drug safety, perinatal depression, pregnancy